Inhibitory Effect of the Noncamptothecin Topoisomerase I Inhibitor LMP-400 on Female Mice Models and Human Pheochromocytoma Cells - Schovanek, Jan; Bullova, Petra; Tayem, Yasin; Giubellino, Alessio; Wesley, Robert; Lendvai, Nikoletta; Nölting, Svenja; Kopacek, Juraj; Frysak, Zdenek; Pommier, Yves; Kummar, Shivaani; Pacak, Karel (Endocrinology, 2015)
Metastatic pheochromocytoma continues to be an incurable disease, and treatment with conventional cytotoxic chemotherapy offers limited efficacy. In the present study, we evaluated a novel topoisomerase I inhibitor, LMP-400, as a potential treatment for this devastating disease. We found a high expression of topoisomerase I in human metastatic pheochromocytoma, providing a basis for the evaluation of a topoisomerase 1 inhibitor as a therapeutic strategy. LMP-400 inhibited the cell growth of established mouse pheochromocytoma cell lines and primary human tumor tissue cultures. In a study performed in athymic female mice, LMP-400 demonstrated a significant inhibitory effect on tumor growth with two drug administration regimens. Furthermore, low doses of LMP-400 decreased the protein levels of hypoxia-inducible factor 1 (HIF-1α), one of a family of factors studied as potential metastatic drivers in these tumors. The HIF-1α decrease resulted in changes in the mRNA levels of HIF-1 transcriptional targets. In vitro, LMP-400 showed an increase in the growth-inhibitory effects in combination with other chemotherapeutic drugs that are currently used for the treatment of pheochromocytoma. We conclude that LMP-400 has promising antitumor activity in preclinical models of metastatic pheochromocytoma and its use should be considered in future clinical trials.
Keywords: Benzodioxoles; nádory jater; nádory plic; Isoquinolines; Lung Neoplasms; myši nahé; regulace genové exprese u nádorů; Humans; PC12 Cells; DNA Topoisomerases, Type I; Tumor Cells, Cultured; Adrenal Gland Neoplasms; Pheochromocytoma; hypoxie buňky; buňky PC12; Dose-Response Relationship, Drug; Female; Drug Synergism; Antineoplastic Agents; polymerázová řetězová reakce s reverzní transkripcí; Blotting, Western; krysa rodu Rattus; DNA-topoisomerasy I; Mice, Nude; lidé; Reverse Transcriptase Polymerase Chain Reaction; zvířata; proliferace buněk; Hypoxia-Inducible Factor 1, alpha Subunit; Liver Neoplasms; synergismus léků; benzodioxoly; nádorové buňky kultivované; faktor 1 indukovatelný hypoxií - podjednotka alfa; inhibitory topoisomerasy I; Topoisomerase I Inhibitors; ženské pohlaví; Cell Proliferation; nádorové buněčné linie; protinádorové látky; nádory nadledvin; Rats; vztah mezi dávkou a účinkem léčiva; Animals; Cell Line, Tumor; western blotting; Gene Expression Regulation, Neoplastic; Disease Models, Animal; Cell Hypoxia; isochinoliny; feochromocytom; modely nemocí na zvířatech